8000 years of environmental evolution of barrier–lagoon systems emplaced in coastal embayments (NW Iberia). (November 2015) - González-Villanueva, Rita; Pérez-Arlucea, Marta; Costas, Susana; Bao, Roberto; Otero, Xose L; Goble, Ronald
The rocky and indented coast of NW Iberia is characterized by the presence of highly valuable and vulnerable, small and shallow barrier–lagoon systems structurally controlled. The case study was selected to analyse barrier–lagoon evolution based on detailed sedimentary architecture, chronology, geochemical and biological proxies. The main objective is to test the hypothesis of structural control and the significance at regional scale of any high-energy event recorded. This work is also aimed at identifying general patterns and conceptualizing the formation and evolution of this type of coastal systems. The results allowed us to establish a conceptual model of Holocene evolution that applies to rock-bounded barrier–lagoon systems. The initial stage (early Holocene) is characterized by freshwater peat sedimentation and ended by marine flooding. The timing of the marine flooding depends on the relation between the elevation of the basin and the relative mean sea-level position; the lower the topography, the earlier the marine inundation. Thus, the age of basin inundation ranged from 8 to 4 ka BP supporting significant structural differences. Once marine inundation occurred, all systems followed similar evolutionary patterns characterized by a phase of landward barrier migration and aeolian sedimentation towards the back-barrier (i.e. retrogradation) that extended circa 3.5 ka BP. The later phases of evolution are characterized by a general trend to the stabilization of the barriers and the infilling of the lagoons. This stabilization may be temporally interrupted by episodes of enhanced storminess or sediment scarcity. In this regard, washover deposits identified within the sedimentary architecture of the case study explored here suggest pervasive high-energy events coeval with some of the cooling events identified in the North Atlantic during the mid- to late Holocene.